Identification of Indicators for Evaluating Reclamation and Post-Mining Policies Towards Compliance by Companies in Jambi Province in Environmental Aspects - Amril Fadli; Bunga Mardhotillah (ILAW, 2026)
Mining activities in Jambi Province significantly contribute to economic growth but pose severe threats to environmental sustainability. Despite existing regulations, company compliance regarding reclamation and post-mining obligations remains a critical challenge. Evaluating these policies requires a clear, standardized set of indicators to measure compliance effectively. This study aims to identify and formulate key performance indicators (KPIs) for evaluating reclamation and post-mining policies, specifically focusing on enhancing company compliance with environmental aspects in Jambi Province. This study employs a mixed-methods approach combining qualitative and quantitative analyses. Data were gathered through legal desk research, deep interviews with environmental experts, government officials, and mining representatives, followed by a Delphi survey to validate the indicators. The Analytical Hierarchy Process (AHP) was utilized to prioritize and weight the identified indicators. The study successfully identified four main dimensions of indicators: Ecological Restoration (soil quality, revegetation success, biodiversity index), Financial Assurance (reclamation bond placement, budget realization), Legal-Administrative Compliance (reporting punctuality, document conformity), and Social-Environmental Impact (acid mine drainage control, local community satisfaction). Ecological restoration and financial assurance emerged as the highest-weighted priorities for ensuring long-term environmental sustainability. The formulated indicators provide a robust, measurable framework for local governments to monitor, audit, and evaluate mining companies' compliance. Implementing these structured indicators will strengthen policy enforcement and accelerate successful post-mining rehabilitation in Jambi Province.